Inside the Matrix: Immersive Live Coding for Architectural Design. (June 2021) - Castelo-Branco, Renata; Brás, Catarina; Leitão, António Menezes
Algorithmic Design (AD) uses computer programs to describe architectural models. These models are visual by nature and, thus, greatly benefit from immersive visualization. To allow architects to benefit from the advantages of Virtual Reality (VR) within an AD workflow, we propose a new design approach: Live Coding in Virtual Reality (LCVR). LCVR means that the architect programs the design while immersed in it, receiving immediate feedback on the changes applied to the program. In this paper, we discuss the benefits and impacts of such an approach, as well as the most pressing implementation issues, namely the projection of the programming environment onto VR, and the input mechanisms to change the program or parts of it. For each, we offer a critical analysis and comparison of the various solutions available in the context of two different programming paradigms: visual and textual.